Proceso de atención de enfermería en paciente de 4 años de edad con enfermedad mano – pie – boca. - Monserrate Ramos, Alina Dayana (2023)
Hand-foot-mouth disease is caused by a highly transmissible infection caused by enterovirus 71 and Coxsackie A16. Transmission occurs by the fecal-oral route and through contaminated objects. This case study is based on a 4-year-old male pediatric patient with hand-foot-mouth disease who attended the clinic due to the appearance of painful vesicles on the oral mucosa, dysphagia, and rash on the upper extremities and lower. The clinical study intends to apply a nursing care process in a 4-year-old patient diagnosed with hand-foot-mouth disease, to perform nursing care that guarantees patient recovery The methods used in the study are observation, interview and exhaustive follow-up of the patient, emphasizing their personal and family history, complementary examinations, among others. On the other hand, the research makes an extensive review of bibliographies to correlate the information with the clinical picture. Finally, the results obtained during the execution of the case were the identification of its clinical manifestations through the physical examination, the creation of a nursing diagnosis and the execution of interventions taking into account the need for treatment.